Odpowiedź :
[tex]zad.13\\\\a)~~\dfrac {4}{7} \div 3=\dfrac {4}{7} \div \dfrac{3}{1}=\dfrac {4}{7} \cdot \dfrac{1}{3}=\dfrac{4}{21} \\\\b)~~\dfrac {9}{10} \div 6=\dfrac {9}{10} \div \dfrac{6}{1}=\dfrac {9}{10} \cdot \dfrac{1}{6}=\dfrac{3}{20} \\\\c)~~1\dfrac {1}{7} \div 8=\dfrac {8}{7} \div \dfrac{8}{1}=\dfrac {8}{7} \cdot \dfrac{1}{8}=\dfrac{1}{7} \\\\d)~~2\dfrac {2}{5} \div 4=\dfrac {12}{5} \div \dfrac{4}{1}=\dfrac {12}{5} \cdot \dfrac{1}{4}=\dfrac{3}{5}[/tex]
[tex]zad.12\\\\a)~~(1\frac{4}{5} \div \frac{3}{7} )\div 1\frac{2}{5} =(\frac{9}{5} \div \frac{3}{7} )\div 1\frac{2}{5}=(\frac{9}{5} \cdot \frac{7}{3} )\div 1\frac{2}{5}=\frac{21}{5} \div \frac{7}{5} =\frac{21}{5} \cdot \frac{5}{7} =\frac{3}{1} =3\\\\[/tex]
[tex]b)~~3\frac{3}{4} \div (2\frac{1}{6} -1\frac{1}{2} )=3\frac{3}{4} \div (2\frac{1}{6} -1\frac{3}{6} )=3\frac{3}{4} \div (\frac{13}{6} -\frac{9}{6} )=3\frac{3}{4} \div \frac{4}{6}=\frac{15}{4} \div \frac{2}{3}=\frac{15}{4} \cdot \frac{3}{2}==\frac{45}{8} =5\frac{5}{8}[/tex]
12.
a)
[tex](1 \frac{4}{5} \div \frac{3}{7} ) \div 1 \frac{2}{5} = ( \frac{9}{5} \times \frac{7}{3} ) \div \frac{7}{5} = ( \frac{3}{5} \times \frac{7}{1} ) \times \frac{5}{7} = \frac{21}{5} \times \frac{5}{7} = \frac{3}{1} \times \frac{1}{1} = 3[/tex]
b)
[tex]3 \frac{3}{4} \div (2 \frac{1}{6} - 1 \frac{1}{2} ) = \frac{15}{4} \div ( 2 \frac{1}{6} - 1 \frac{3}{6} ) = \frac{15}{4} \div (1 \frac{7}{6} - 1 \frac{3}{6} ) = \frac{15}{4} \div \frac{4}{6} = \frac{15}{4} \times \frac{6}{4} = \frac{15}{2} \times \frac{3}{4} = \frac{45}{8} = 5 \frac{5}{8} [/tex]
13.
a)
[tex] \frac{4}{7} \div 3 = \frac{4}{7} \times \frac{1}{3} = \frac{4}{21} [/tex]
b)
[tex] \frac{9}{10} \div 6 = \frac{9}{10} \times \frac{1}{6} = \frac{9}{60} = \frac{3}{20} [/tex]
c)
[tex]1 \frac{1}{7} \div 8 = \frac{8}{7} \times \frac{1}{8} = \frac{1}{7} \times 1 = \frac{1}{7} [/tex]
d)
[tex]2 \frac{2}{5} \div 4 = \frac{12}{5} \times \frac{1}{4} = \frac{3}{5} \times \frac{1}{1} = \frac{3}{5} [/tex]